The economics of the German investigation of Facebook’s data collection - Oliver Budzinski; Marina Grusevaja; Victoriia Noskova (Market and Competition Law Review)
The importance of digital platforms and related data-driven business models is ever increasing and poses challenges to the workability of competition in the respective markets (tendencies towards dominant platforms, paying-with-data instead of traditional money, privacy concerns, etc.). Due to such challenges, investigations of such markets are of high interest. One of the recent cases is the investigation of Facebook’s data collection practices by German competition authorities. Our article, in contrast to the wide stream of legal studies on this case, aims to analyse whether Facebook’s practices regarding data collection could constitute an abuse of market power from an economic perspective, more specifically against the background of modern data economics. In doing so we summarise the state of the advanced theories, including influences from behavioural economics addressing such markets, and discuss four potential theories of harm.